The Study of the Relationship Between Religious Beliefs Performance and Life Satisfaction Among the Elderly - Masoud Hadjizadeh Meimandi; Mahdi Barghamadi (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: the study of the relationship between religious beliefs performance and life satisfaction among the elderly in Sabzavar city. Methods &  Materials: the data gathered about religious beliefs performance and also life satisfaction among the elderly by survey research and questionnaires in representative sample. The size of sample was 301 old persons and the technique of sampling was clusters sampling. The data analyzed with descriptive statistical tests, correlation coefficient, multiple regression, T test and one-way analysis of varianceTop of Form Bottom of Form Results: the relationships between four domains of religious beliefs performance with life satisfaction wereweekly meaningful, also the difference between the score of life satisfaction and religious beliefs performance were meaningful. In addition, there were meaningful relationship between the scores of life satisfaction of the subjects at the various levels of education. Conclusion: The life satisfaction between those old persons (the elderly) that have more commitment to religious beliefs, were more and this finding is in agreement with Islamic instructions.